Ranolazine Prevents Phenotype Development in a Mouse Model of Hypertrophic Cardiomyopathy - Coppini, Raffaele (Circ Heart Fail, 2017)
BACKGROUND—: Current therapies are ineffective in preventing the development of cardiac phenotype in young carriers of mutations associated with hypertrophic cardiomyopathy (HCM). Ranolazine, a late Na(+) current blocker, reduced the electromechanical dysfunction of human HCM myocardium in vitro. METHODS AND RESULTS—: To test whether long-term treatment prevents cardiomyopathy in vivo, transgenic mice harboring the R92Q troponin-T mutation and wild-type littermates received an oral lifelong treatment with ranolazine and were compared with age-matched vehicle-treated animals. In 12-months-old male R92Q mice, ranolazine at therapeutic plasma concentrations prevented the development of HCM-related cardiac phenotype, including thickening of the interventricular septum, left ventricular volume reduction, left ventricular hypercontractility, diastolic dysfunction, left-atrial enlargement and left ventricular fibrosis, as evaluated in vivo using echocardiography and magnetic resonance. Left ventricular cardiomyocytes from vehicle-treated R92Q mice showed marked excitation–contraction coupling abnormalities, including increased diastolic [Ca(2+)] and Ca(2+) waves, whereas cells from treated mutants were undistinguishable from those from wild-type mice. Intact trabeculae from vehicle-treated mutants displayed inotropic insufficiency, increased diastolic tension, and premature contractions; ranolazine treatment counteracted the development of myocardial mechanical abnormalities. In mutant myocytes, ranolazine inhibited the enhanced late Na(+) current and reduced intracellular [Na(+)] and diastolic [Ca(2+)], ultimately preventing the pathological increase of calmodulin kinase activity in treated mice. CONCLUSIONS—: Owing to the sustained reduction of intracellular Ca(2+) and calmodulin kinase activity, ranolazine prevented the development of morphological and functional cardiac phenotype in mice carrying a clinically relevant HCM-related mutation. Pharmacological inhibitors of late Na(+) current are promising candidates for an early preventive therapy in young phenotype-negative subjects carrying high-risk HCM-related mutations.